PENGARUH PEMANGKASAN dan KONSENTRASI ECO ENZYME terhadap PERTUMBUHAN dan KUALITAS TANAMAN JUNGGULAN (Crassochephalum Crepidioides) - yuni aulia agustin; Mahayu Woro Lestari; Siti Asmaniyah Mardiyani (AGRONISMA, 2021)
This study aims to determine the interaction between pruning treatment and eco-enzyme concentration as well as the effect of pruning and eco-enzyme concentration on the growth and quality of junggulan (Crassocephalum crepidioides) plants. The research was carried out on agricultural land located in Merjosari Village, Lowokwaru District, Malang City with an altitude of + 700 m above sea level, an average air temperature of 20Âº C - 28 C, humidity 79% - 86%, and an average rainfall of 550 mm. The analysis was carried out at the Integrated Laboratory of the Faculty of Agriculture, Islamic University of Malang. The study began in February â€“ March 2021. This study used a Factorial Randomized Block Design (RAK) experiment consisting of 2 factors. Factor 1 is the type of pruning (P) consisting of 2 levels, namely, P0 (without pruning), P1 (pruned 14 days after planting). Factor 2 is the concentration of eco enzyme (E) which consists of 3 levels, namely, E0 (Without eco enzyme), E1 (15 ml/lt water), E2 (30 ml/lt water) from 2 factors obtained 6 combinations, each There were 3 samples of treatment and repeated 3 times so that there were 54 samples. The results showed that there was an interaction between pruning treatment and the concentration of eco-enzyme which tended to give better yields for the yield of junggul plants which were dominated by P1E1 treatment (Pruned 14 hst + 15 ml/lt eco enzyme). In general, the pruning treatment gave the best results for the chlorophyll content. Eco enzyme concentration treatment was able to give a significant effect on the total root length, vitamin C and chlorophyll content.